2010
DOI: 10.5251/abjna.2010.1.3.225.231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation levels and organic compost on okra plants (Abelmoschus esculentus l.) grown in sandy calcareous soil

Abstract: Field experiments were conducted on the growing seasons 2008 and 2009 at a private farm located at a newly reclaimed sandy area, El-Saff, Giza governorate, Egypt to evaluate the drip irrigation levels in combination with equal two types of organic fertilizers for an okra crop. The effect of three irrigation levels 1198.8 (I 1 ), 1798.2 (I 2 ) and 2397.6 (I 3 ) m3/acre with drip in conjunction with two organic fertilizers (composted plant residues and chicken manure at the rate of 6 m 3 / acre ) were studied on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 10 publications
(5 reference statements)
6
41
0
6
Order By: Relevance
“…This finding is consistent with the observation of earlier researchers on the integration of organic manure with inorganic soil-applied fertilizer for okra (Akande et al 2010;Abd El-Kader et al (2010) and other crops such as maize (Makinde and Ayoola 2008), rice (Satyanarayana et al 2007), sorghum (Bayu et al 2006), and sweet maize (Uwah et al 2011). Foliar fertilizers are fast acting because the nutrients are absorbed at the site where they are readily utilized.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This finding is consistent with the observation of earlier researchers on the integration of organic manure with inorganic soil-applied fertilizer for okra (Akande et al 2010;Abd El-Kader et al (2010) and other crops such as maize (Makinde and Ayoola 2008), rice (Satyanarayana et al 2007), sorghum (Bayu et al 2006), and sweet maize (Uwah et al 2011). Foliar fertilizers are fast acting because the nutrients are absorbed at the site where they are readily utilized.…”
Section: Discussionsupporting
confidence: 82%
“…According to Garge and Bahla (2008), PM supplies phosphorous more readily to plants than other organic sources. In another study, Abd El-Kader et al (2010) reported that manure from poultry increased okra yield and water use efficiency than composted plant residue.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that chicken manure has beneficial effects on okra yield. The result is in conformity with earlier investigators, Abd El-Kader et al (2010), Rajpaul et al (2004), Estefanous and Sawan (2003), Rajpaul et al (2004) El-Nemer et al (2005, Faten and Ismaeil (2005) and Siddiqui et al (2009) who reported the beneficial effect of chicken manure on growth and yield of different vegetables.…”
Section: Pod Length: Fromsupporting
confidence: 81%
“…It is a chief vegetable crop grown for its immature pod that can be used as a boiled or fried vegetable, or it may be added to salad or soup (Kashif et al, 2010). Okra plays an immense role in the human diet, providing carbohydrates, fats, proteins, vitamins, and minerals (Abd El-Kader et al, 2010). Okra is rich in unsaturated fatty acids, like linoleic acid, that are generally deficient in the human diet (Savello et al, 1980).…”
Section: Introductionmentioning
confidence: 99%